Dificultad del aprendizaje: Dislexia de los estudiantes de 5to. “C” de la Escuela Fausto Molina Molina - Vallejo Freire, Mónica Lissette (2021)
Dyslexia affects 10% of children worldwide. At the Fausto Molina Molina School, it could be seen that there is no estimate of the students who have dyslexia, which could cause unfair treatment in children who suffer from this difficulty, children tend to bully them and teachers do not know their condition gives them unfair treatment, on the other hand, parents are ignorant of dyslexia in their children. As the research is aimed at reducing the risks run by children from the 5th “C” of the Fausto Molina Molina School with poor school performance due to undiagnosed dyslexia, this place is chosen precisely because it has reference to the fact that there are children with symptoms of dyslexia. The main objective of the thesis is the Diagnosis of learning difficulties due to Dyslexia, in order to know the subject in depth, concepts such as the type of dyslexia, warning signs in children with dyslexia problems, among others, were addressed. In the development of the results it was possible to verify the hypotheses, in the investigation the analytical and deductive methods were of great help. The most relevant conclusion is that of the results obtained where it was evidenced that parents have no idea whether or not their children have dyslexia, for which it was recommended that parents should take their children to a comprehensive health assessment to that can treat dyslexia in time.